Accessibility Analysis of Digital Libraries and Specialized Library Resources - Tiurkedzhy, N. S.; Davydova, I. O.; Marina, O. Yu.; Marin, S. O.; Тюркеджи, Наталя Станіславівна (Український державний університет науки і технологій, 2022)
Objective. The article focuses on the current state of library web content accessibility. Methods. 56 library websites of different countries (27 digital libraries and 29 specialized library resources for people with disabilities) have been successfully tested for the compliance with the WCAG 2.1 standards using the Webaccessibility.com service. Using the Alexa.com service the comparative analysis of the websites traffic ranking has been additionally conducted. Results. It has been established that only 3 websites out of 56 meet the accessibility standards of WCAG 2.1 with the compliance score of 92%. Conclusions. It has been concluded that the libraries' current practices of providing web content accessibility are insufficient. The emphasis has been placed on the need to optimize and promote specialized library resources and to implement a continuous audit of web content accessibility by means of automatic testing and engaging users with disabilities into these processes. Мета. Дослідження сучасного стану доступності бібліотечного веб-контенту. Методика. 56 бібліотечних веб-сайтів різних країн (27 цифрових бібліотек та 29 спеціалізованих бібліотечних ресурсів для людей з обмеженими можливостями) пройшли успішну перевірку на відповідність стандартам WCAG 2.1 за допомогою сервісу Webaccessibility.com. За допомогою сервісу Alexa.com додатково проведено порівняльний аналіз рейтингу відвідуваності сайтів. Результати. Встановлено, що лише 3 веб-сайти з 56 відповідають стандартам доступності WCAG 2.1 з показником відповідності 92%. Висновки. Зроблено висновок, що існуючі в бібліотеках практики забезпечення доступності веб-контенту є недостатніми. Акцент було зроблено на необхідності оптимізації та просування спеціалізованих бібліотечних ресурсів та впровадження постійного аудиту доступності веб-контенту шляхом автоматичного тестування та залучення до цих процесів користувачів з обмеженими можливостями.
Аналіз доступності цифрових бібліотек та спеціалізованих бібліотечних ресурсів
Tiurkedzhy N. S. – ORCID: 0001-6785-2900
Keywords: digital library; digital library website; digital library for persons with disabilities; website accessibility; web accessibility; web accessibility for people with disabilities; web content accessibility guidelines; WCAG 2.1; цифрова бібліотека; веб-сайт цифрової бібліотеки; цифрова бібліотека для людей з обмеженими можливостями; доступність веб-сайту; веб-доступність; веб-доступність для людей з обмеженими можливостями; рекомендації щодо доступності веб-контенту